Intellectual Property Licences and Technology Transfer : a Practical Guide To The New European Licensing Regime - Curley, Duncan (Chandos Publishing, 2004)
This essential guide vital new changes by the European Commission to the law governing the enforceability of intellectual property licences in Europe. Agreements which contain the grant of a licence by one party to another of intellectual property rights are subject to European competition (anti-trust) laws. In particular, many agreements containing licences of patent rights and rights in confidential information and technical know-how are caught by Article 81(1) of the EC Treaty, which prohibits agreements between undertakings which prevent, restrict or distort competition in the Common Market. However, because licences of intellectual property rights usually facilitate the transfer of technology from one undertaking to another, and the licensor and licensee will often operate at different levels of the market, many licences of intellectual property rights may benefit from an automatic exemption under Article 81(3) of the EC Treaty. On 1 May 2004, this exemption is being radically overhauled, as part of the European Commission's drive to modernise European competition law. This book examines the changes in that legislation. The legislation is completely new and there is therefore no existing book on the marketThe change in the law will require an entirely new approach to the drafting of IP licencesThe change in the law will require existing IP licences to be re-examined and possibly re-negotiated.